High-performance III-V MOSFET with nano-stacked high-k gate dielectric and 3D fin-shaped structure - Chen, Szu-Hung (Springer, 2012)
A three-dimensional (3D) fin-shaped field-effect transistor structure based on III-V metal-oxide-semiconductor field-effect transistor (MOSFET) fabrication has been demonstrated using a submicron GaAs fin as the high-mobility channel. The fin-shaped channel has a thickness-to-width ratio (T(Fin)/W(Fin)) equal to 1. The nano-stacked high-k Al(2)O(3) dielectric was adopted as a gate insulator in forming a metal-oxide-semiconductor structure to suppress gate leakage. The 3D III-V MOSFET exhibits outstanding gate controllability and shows a high I(on)/I(off) ratio > 10(5) and a low subthreshold swing of 80 mV/decade. Compared to a conventional Schottky gate metal–semiconductor field-effect transistor or planar III-V MOSFETs, the III-V MOSFET in this work exhibits a significant performance improvement and is promising for future development of high-performance n-channel devices based on III-V materials.